Impedance bridges: from Wheatstone to Josephson. (27th July 2018) - Overney, Frédéric; Jeanneret, Blaise
Abstract: This paper reviews the recent evolution of the measurement techniques in the area of impedance measurement from the Wheatstone bridge to the most advanced Josephson-based digital impedance bridge. The progress in the development of high sampling rate, high accuracy digital-to-analog and analog-to-digital converters has led to the development of digital impedance bridges that have profoundly modified the landscape of impedance metrology. Although these new bridges do not yet outperform the traditional transformer-based bridge in terms of accuracy, they significantly improve their measurement capabilities and flexibility by allowing a complete automation, a full coverage of the complex plane, arbitrary bridge ratios and extended frequency range. In addition, after the redefinition of the International System of Unit, they will contribute to the realization of the henry and the farad by establishing a direct link between the quantized Hall resistance and the capacitance or inductance standards.